Autoantibodies Targeting AT1 Receptor from Patients with Acute Coronary Syndrome Upregulate Proinflammatory Cytokines Expression in Endothelial Cells Involving NF-κB Pathway - Weijuan Li; Zhi Li; Yaoqi Chen; Songhai Li; Yuanyuan Lv; Wenping Zhou; Mengyang Liao; Feng Zhu; Zihua Zhou; Xiang Cheng; Qiutang Zeng; Yuhua Liao; et al. (Journal of Immunology Research)
Our study intended to prove whether agonistic autoantibodies to angiotensin II type 1 receptor (AT1-AAs) exist in patients with coronary heart disease (CHD) and affect the human endothelial cell (HEC) by upregulating proinflammatory cytokines expression involved in NF-κB pathway. Antibodies were determined by chronotropic responses of cultured neonatal rat cardiomyocytes coupled with receptor-specific antagonists (valsartan and AT1-EC2) as described previously. Interleukin-6 (IL-6), vascular cell adhesion molecule-1 (VCAM-1), and monocyte chemotactic protein-1 (MCP-1) expression were improved at both mRNA and protein levels in HEC, while NF-κB in the DNA level was improved detected by electrophoretic mobility shift assays (EMSA). These improvements could be inhibited by specific AT1 receptor blocker valsartan, NF-κB blocker pyrrolidine dithiocarbamate (PDTC), and specific short peptides from the second extracellular loop of AT1 receptor. These results suggested that AT1-AAs, via the AT1 receptor, induce expression of proinflammatory cytokines involved in the activation of NF-κB. AT1-AAs may play a great role in the pathogenesis of the acute coronary syndrome by mediating vascular inflammatory effects involved in the NF-κB pathway.